Parent directiveness in free play with young children with physical impairments. - Cress CJ; Moskal L; Hoffmann A (Communication Disorders Quarterly, 2008)
Children with disabilities are reported to experience a high degree of directive parent interaction compared to typically developing children because of poor communicative or task skills. This study examines relationships between parent behaviors (directiveness and contingency) and child skills (language and motor) for children with physical or neuromotor impairments at risk for being nonspeaking during undirected incidental play. The only correlation between parent behavior and child developmental status was between physical directiveness and child motor scores. Previous reports of high directiveness that increase with degree of disability might be attributable to task instructions during object play, in which high physical directiveness would be required for this population.